A SETTLEMENT OPTION OF LAND IN THE KRUGER NATIONAL PARK - MMETHI, HELEN MOKITLELO (My University, 2011)
South Africa ushered in its land policy in 1997. This policy makes provision for various programmes but this research hinges on the aspects of the land restitution programme. There are four settlement options that are being stipulated in the act, but one particular settlement option is the general option and is being embraced in settling the land claims within the protected area, especially National Parks. The purpose of this study was to determine the challenges that are associated with the settlement option of land claims in the national parks particularly the Kruger National Park. The study was approached from perspective of policy implementation, since the assumed challenges are imbedded within the transaction of the restitution policy. The study design opted for and applied was a qualitative method and interviews were conducted with the concerned role players. One of the main findings is that there are no apparent economic benefits to the claimant communities when this option is employed; thus the empowerment policy objective is defeated. Stakeholders would prefer an alternative settlement option or an overhaul of policy
MM thesis - P&DM
Keywords: Land claim settlements; Kruger National Park